930Development and feasibility of a mHealth supported Comprehensive Intervention Model ("CIMmH") for esophageal cancer patients. (2nd September 2021) - Xu, He; Xv, He; Guo, Yan
Abstract: Background: Esophageal cancer patients often experience a clinically relevant deterioration of quality of life (QoL) after esophagectomy due to malnutrition, lack of physical exercise, and psychological problems. This study aims to evaluate the feasibility and efficacy of a comprehensive intervention model using the mHealth system (CIMmH) on the mobile platform that offers accessible nutritional, exercise, and psychosocial support to esophageal cancer patients after esophagectomy. Methods: Twenty esophageal cancer patients were invited to join the CIMmH for 12 weeks. The CIMmH included an online component and an offline consultation component. The participants were assessed before surgery and at 1-month and 3-month intervals after esophagectomy. QoL, depressive symptoms, anxiety, stress, nutrition, and physical fitness were measured. Results: Sixteen out of 20 (80%) completed the program. One month after esophagectomy, the global health scale significantly decreased while fatigue, pain, and dyspnea increased. At the 3-month follow-up, only pain, difficulty with eating, dry mouth and trouble with talking were significantly worse than the baseline. All other dimensions in the QoL returned to the preoperative level. Weight and BMI were reduced throughout the study and no significant changes were observed in physical fitness. Depressive symptoms significantly increased one month after surgery. Conclusions: The CIMmH had good feasibility and demonstrated encouraging preliminary efficacy for enhancing recovery after surgery among esophageal cancer patients in China. Key messages: Esophageal cancer, Quality of life, Nutrition, Physical exercise, Psychological support, Mobile Health (mHealth)